Support for indirect victimization in deliberate murder in Iran and international documents. - siros parvizi; rahim davarnia (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2020)
In the domestic law, the damage to the murdered family as a result to the deliberate killing of the murdered family has not paid special attention and the offender or community has no obligation to survive the victim’s survivors. However, the loss of a member of the family faces other members of the pupulation with various crises and provides a source for many deviations and problems in the family and society, especially if the lost member is a family leader. In this article concluded that the crime of internation murder in addition to the direct victim (victim) has an indirect victim ( such as a parent and victimized) in the first step and in the next step, be supported by the legislator and the community. In this way , it is clear from the examination of domestic law that the definition of victim includes relatives and victims of the victim and on the basis of various legal, religious and rational principles, it should be supported in various international documents as well. Victim survivors have been used and member states have been required to support this group of victims.